THE ROLE OF FORESTS IN WATER CYCLE REGULATION AND FLOOD CONTROL - Nguyen Tuan Anh; Nam Peng; Le Hoang Nam (Yayasan Adra Karima Hubbi, 2025)
Forests play a crucial role in regulating the water cycle and controlling flood risks, serving as natural buffers against extreme weather events. The ability of forests to influence local hydrological cycles through processes like transpiration, infiltration, and water retention is essential for maintaining ecosystem balance and human livelihoods. However, deforestation and land-use changes are significantly altering these processes, leading to increased flood risks and water scarcity in many regions. This study aims to explore the role of forests in water cycle regulation and their effectiveness in flood control, with a focus on identifying the mechanisms through which forests influence hydrological processes. The research also seeks to evaluate the impact of forest degradation on flood intensity and water resource availability. A mixed-methods approach was employed, combining remote sensing data, hydrological modeling, and field observations. Data were collected from three forested regions with varying degrees of human activity. Water flow rates, soil moisture levels, and vegetation cover were monitored across these sites to assess the hydrological impact of forest ecosystems on local water systems. The findings indicate that intact forests significantly reduce flood risks by enhancing water infiltration and promoting soil retention. Deforestation and land degradation led to higher surface runoff, reduced groundwater recharge, and increased flood occurrence. Forests with greater biodiversity showed more resilience in maintaining these functions. The study concludes that forests are vital to water cycle regulation and flood mitigation. Conservation and restoration of forest ecosystems are essential for maintaining hydrological stability and reducing the adverse impacts of floods.